Monoclonal Antibodies Targeting Alarmins: A New Perspective for Biological Therapies of Severe Asthma - Corrado Pelaia; Giulia Pelaia; Federico Longhini; Claudia Crimi; Cecilia Calabrese; Luca Gallelli; Angela Sciacqua; Alessandro Vatrella (Biomedicines, 2021)
Alarmins are innate cytokines, including thymic stromal lymphopoietin (TSLP), interleukin-33 (IL-33), and interleukin-25 (IL-25), which are mainly produced by airway epithelium and exert a prominent role in asthma pathobiology. In particular, several environmental factors such as allergens, cigarette smoking, airborne pollutants, and infectious agents trigger the release of alarmins, which in turn act as upstream activators of pro-inflammatory pathways underlying type 2 (T2-high) asthma. Indeed, alarmins directly activate group 2 innate lymphoid cells (ILC2), eosinophils, basophils, and mast cells and also stimulate dendritic cells to drive the commitment of naïve T helper (Th) cells towards the Th2 immunophenotype. Therefore, TSLP, IL-33, and IL-25 represent suitable targets for add-on therapies of severe asthma. Within this context, the fully human anti-TSLP monoclonal antibody tezepelumab has been evaluated in very promising randomized clinical trials. Tezepelumab and other anti-alarmins are thus likely to become, in the near future, valuable therapeutic options for the biological treatment of uncontrolled severe asthma.